Peningkatan Literasi Keuangan dan Manajemen Diri bagi Young Entrepreneurs Mahasiswa Politeknik Negeri Ujung Pandang - Maryam Nadir; Rasyidah Nadir; Tawakkal Tawakkal; Kartini Kartini (Lembaga Pengembangan Kinerja Dosen, 2026)
Financial Literacy is a crucial aspect in supporting the success of a business for young entrepreneurs, especially in preparing financial reports. Financial literacy encompasses knowledge of money management, investment, and financial planning, while self-management encompasses skills such as time discipline, emotional control, and decision-making.